Bending Moment Responses Of Bridge Pile Foundation In A Liquefiable Soil Stratum Underlain By Irregular Bedrock Under Earthquakes - Ming Narto Wijaya (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2015)
In the past earthquakes, there have been many reports about damage to bridge’s pile foundations caused by soil liquefaction. The purpose of this study is to investigate the bending moment responses of pile foundations of a bridge pier in a liquefiable soil stratum underlain by irregular bedrock under earthquakes. In this study, the effect of irregular bedrock on the bending moment responses of pile is investigated using nonlinear three-dimensional effective stress finite element method. The slope variation of inclined lateral rock and local intrusion of bedrock and two types of connection between pile cap and piles were considered in the analysis: fixed connection and hinge connection. Three acceleration time-histories were used as input motion. From the parametric studies, it was found that the effect of irregular bedrock on the bending moment responses of pile depends on the characteristics of earthquake motions, location of pile within the pile group and sometimes the configuration of the irregular bedrock. Therefore, it is important to check the adequacy of pile foundation design using the earthquake motions measured at the construction site whose bedrock configuration should be determined as accurately as possible.